Exploring local perceptions of climate change impact and adaptation in rural Bangladesh - Davis, Peter; Ali, Snigdha (International Food Policy Research Institute, 2014)
This paper reports on findings from 30 focus group discussions and 30 key informant interviews conducted in 12 districts of Bangladesh in May 2012. The discussions and interviews draw attention to perceptions of climate change and how climate-related trends influence people’s lives, both directly and indirectly. The findings also identify how people adapt to and cope with these changes. This paper aims to improve our understanding of local people’s perceptions of these changes, explore the ways they are affected by them, and how well they are adapting to them. In order for policymakers to plan responses to climate change in Bangladesh, it is essential to understand how people understand and cope with these trends.